Joseph G. Fucilla, Studies and notes (literary and historical). Istituto Editoriale del Mezzogiorno, Napoli-Roma, 1953; 418 pp. - Alatorre, Antonio (El Colegio de México, 1958)
Se reseñó el libro: Studies and notes (literary and historical).